Deskripsi Kesulitan Belajar Siswa SMAN 3 Padang Panjang Pada Materi Asam Basa Kelas XI SMA/MA - Rizki Rahmadhani; Guspatni Guspatni (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
Acid-base topic is considered as a difficult topic by high school students of SMAN 3 Padang Panjang. This is proofed by the result of their mark that showed 80.2% of 101 students do not past the test. This is an indication that the students hava a learning difficulties. Learning difficulties is the condition where someone has an obstacle in learning about something. This research intend to identify the student’s learning difficulties on acid-base topic and find out the factors of their learning difficulties. The method of this research is descriptive method. The sample of this research are 32 students of class XI IPA 3 SMAN 3 Padang Panjang. And from the research, researcher find out that the percentage of learning difficulties indication of the sample is 46.8% with the category is high enough. This learning difficulties are influenced by scheduling and implementation of learning factors.